2022
DOI: 10.3390/foods11213431
|View full text |Cite
|
Sign up to set email alerts
|

An Insight on the Biomedical Potential of Portuguese Propolis from Gerês

Abstract: Osteoarthritis (OA), a progressive degenerative disease of weight-bearing joints, is the second leading cause of disability in the world. Despite all the advances and research over the last years, none of the proposed strategies has been effective in generating functional and long-lasting tissue. Due to the high prevalence of OA and the urgent need for an effective and successful treatment, interest in natural products as anti-inflammatory agents, such as propolis and its components, has emerged. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…The percentage inhibition of protein denaturation of the seasonal SPE was within the range of 81.67% to 100% at the concentration range of 6.25 to 50 µg/mL, while DS presented its inhibitory effect within the range of 79.16% to 111.45% at the same concentration range. A previous study revealed that the hydroalcoholic extracts of Portuguese propolis were able to inhibit the denaturation of BSA protein by 24.93% to 74.69% [31], which are lower values than those obtained for the seasonal SPE (81.67% to 100%). Afonso et al [32] also evaluated the anti-inflammatory potential of ethanolic extracts of Portuguese propolis and found that they inhibited protein denaturation by 28-45%.…”
Section: Effect Of Spe and Spc On Protein Denaturationmentioning
confidence: 63%
“…The percentage inhibition of protein denaturation of the seasonal SPE was within the range of 81.67% to 100% at the concentration range of 6.25 to 50 µg/mL, while DS presented its inhibitory effect within the range of 79.16% to 111.45% at the same concentration range. A previous study revealed that the hydroalcoholic extracts of Portuguese propolis were able to inhibit the denaturation of BSA protein by 24.93% to 74.69% [31], which are lower values than those obtained for the seasonal SPE (81.67% to 100%). Afonso et al [32] also evaluated the anti-inflammatory potential of ethanolic extracts of Portuguese propolis and found that they inhibited protein denaturation by 28-45%.…”
Section: Effect Of Spe and Spc On Protein Denaturationmentioning
confidence: 63%
“…Propolis has also demonstrated anti-aging potential by avoiding premature senescent phenotypes in yeast [ 57 ]. It is worth mentioning that Portuguese propolis may exhibit anti-inflammatory effects in vitro, similar to those obtained from aspirin [ 32 ]. Some studies even suggest a synergistic effect of the various compounds found in propolis, reducing oxidative stress and influencing glucose and cholesterol plasma levels associated with aging [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have observed that treatment with aqueous propolis in rats with radiation-induced arthritis significantly outperforms diclofenac, effectively preventing cartilage breakdown and inhibiting the increase in nitric oxide (NO) [ 31 ]. Additionally, propolis has shown promise in improving mechanical hyperalgesia and gait patterns in an induced osteoarthritis (OA) model, primarily due to its anti-inflammatory and antioxidant properties [ 32 ]. Treatment with propolis in chondrocytes stimulated with IL-1β has demonstrated beneficial effects, including reduced production of NO, decreased expression of MMP13, and increased expression of COL2A1, indicating its potential anti-inflammatory effects in vitro [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Portuguese propolis characteristics have been explored, with researchers being focused on the chemical and biological characterization of samples from different regions of the country [14,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Following this research trend on Portuguese propolis, some studies emphasized the interesting properties of propolis from Gerês, namely an outstanding antioxidant activity [25,28] and the widely known antibacterial and antifungal activities [25,28,30], as well as an anti-inflammatory [26] and anticancer potential [19,22]. Moreover, ethanol extracts of propolis from Gerês have shown unique and consistent biological and chemical profiles over the years [25], holding great potential for establishing standardized criteria for the assessment of Portuguese and Poplar propolis quality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ethanol extracts of propolis from Gerês have shown unique and consistent biological and chemical profiles over the years [25], holding great potential for establishing standardized criteria for the assessment of Portuguese and Poplar propolis quality. However, despite the extensive research on the biological and chemical aspects of these propolis extracts [19,22,26,30,31], comprehensive research regarding the raw/unprocessed propolis samples is currently missing. Considering this, our study aims to evaluate the quality parameters of unprocessed samples collected from Gerês over four consecutive years (2019-2022) and determine their impact on the chemical composition, antioxidant capacity and antimicrobial activity of the ethanol extracts (G.EEs) derived from the same raw samples.…”
Section: Introductionmentioning
confidence: 99%